2022
DOI: 10.3390/children9020259
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of Black Youth Affected by Community Violence: Family and School Context as Pathways to Resilience

Abstract: Black youth who experience community violence occupy multiple environments with varying levels of influence on how they display resiliency to prevent adverse mental health outcomes. Considering the recent rise of mental health concerns (i.e., increase in suicidal outcomes) among Black youth, along with the abundance of research illustrating the detrimental impact of community violence, more research is needed to examine how different environmental factors (e.g., family and school) shape how youth protect their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Building positive relationships can help BMoC feel safe and trust others, learn new ways to relate to people, and develop compassion [ 42 , 43 ]. A recent study found that strong familial relationships, parental bonding, and a positive school climate can help Black youths build resilience in the face of exposure to community violence [ 44 ]. Furthermore, leveraging relationships with leaders in the community, such as teachers, barbers, or persons of faith, can help destigmatize conversations about mental health [ 29 ].…”
Section: The Restorative Integral Support (Ris) Modelmentioning
confidence: 99%
“…Building positive relationships can help BMoC feel safe and trust others, learn new ways to relate to people, and develop compassion [ 42 , 43 ]. A recent study found that strong familial relationships, parental bonding, and a positive school climate can help Black youths build resilience in the face of exposure to community violence [ 44 ]. Furthermore, leveraging relationships with leaders in the community, such as teachers, barbers, or persons of faith, can help destigmatize conversations about mental health [ 29 ].…”
Section: The Restorative Integral Support (Ris) Modelmentioning
confidence: 99%
“…Children are embedded in the community; underprivileged circumstances might encourage delinquent behaviour and affect children’s mental health (Garbarino et al, 1991; Boyd et al, 2022). In Kashmir, due to community-based violence and street protests (Ganie, 2023), another study has proved that contact with extremist groups, fear of raids and arrests foster more excellent deviant behaviours among minors (Dar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Adversity is multifarious and has been associated with conditions that affect everyday life experiences and developmental outcomes of children and their caregivers with widespread negative consequences. These conditions, often including poverty, socioeconomic disadvantage (Béné et al, 2014), community violence (Boyd et al, 2022), and social isolation, can take a toll on families, leading to family disruptions (Nurco et al, 1996), compromised parenting, and elevated risk for compromised health and overall development (Murry, 2019). Notably, those who are able to overcome and navigate adversity appear to be stronger and better prepared for future adversities, demonstrating resilience (Fraser et al, 1999; Patel et al, 2017; Walsh, 2003).…”
mentioning
confidence: 99%